Identification of factors and economic sustainability for Johor Bahru district [electronic resource] - Mokhairulamri Mohd.@Mohamad, 1987- 493647 (2010)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Pengurusan Binaan)) - Universiti Teknologi Malaysia, 2010